IDEOLOGI MANUSIA MENURUT ERICH FROMM (PERPADUAN PSIKOANALISIS SIGMUND FREUD DAN KRITIK SOSIAL KARL MARX) - Sutikna, Nana (Jurnal Filsafat "WISDOM", 2008)
AbstractHuman being needs to be understood deeply by exploringfundamental characters. The fundamental characters have a set of dichotomised situation. Personally, in the process of thinking and behaving, people try to solve those dichotomised problems. The attempts can be seen in the form of character and orientation desired. These are ideology. The ideology determines attitudes and ideas undeliberately fight his human existence. The ideology correlates with conflict situations of human. This obligates free choices according to his fundamental attitudes.Erich Fromm solved the problem which is relevant to theideology by making the concept ofâ€™ to beâ€™, in human potencies be confronted with concept of â€˜to haveâ€™ which signed by productive activity, autonomous, critical, and freedom.Keywords : Human being, Dichotomy, Ideologi, â€œto beâ€